2021
DOI: 10.1002/adma.202005798
|View full text |Cite
|
Sign up to set email alerts
|

Designing Copper‐Based Catalysts for Efficient Carbon Dioxide Electroreduction

Abstract: The electroreduction of carbon dioxide (CO2) has been emerging as a high‐ potential approach for CO2 utilization using renewables. When copper (Cu) based catalysts are used, this platform can produce multi‐carbon (C2+) fuels and chemicals with almost net‐zero emission, contributing to the closure of the anthropogenic carbon cycle. Nonetheless, the rational design and development of Cu‐based catalysts are critical toward the realization of highly selective and efficient CO2 electroreduction. In this review, fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
130
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(146 citation statements)
references
References 196 publications
1
130
0
Order By: Relevance
“…[38] The *CO species adsorbed on Cu surface with different configuration, namely, atop-, bridge-, and hollow-bound CO, in which the CO species coordinate with one, two, and more than three Cu atoms, respectively. [3,39,40] The adsorption states of *CO strongly determine the binding energy of *CO on Cu surface, which is crucial for further hydrogenation process and regulates product distribution. [15,21] This also explains the capability of Cu for catalyzing CO 2 electroreduction to hydrocarbons and multi-carbon products.…”
Section: Reaction Mechanisms Of Co 2 -To-ethylene and Ethanol On Cu-b...mentioning
confidence: 99%
See 2 more Smart Citations
“…[38] The *CO species adsorbed on Cu surface with different configuration, namely, atop-, bridge-, and hollow-bound CO, in which the CO species coordinate with one, two, and more than three Cu atoms, respectively. [3,39,40] The adsorption states of *CO strongly determine the binding energy of *CO on Cu surface, which is crucial for further hydrogenation process and regulates product distribution. [15,21] This also explains the capability of Cu for catalyzing CO 2 electroreduction to hydrocarbons and multi-carbon products.…”
Section: Reaction Mechanisms Of Co 2 -To-ethylene and Ethanol On Cu-b...mentioning
confidence: 99%
“…formed from CO 2 RR, ethylene and ethanol are highly desired because the widely industrial applications with the huge market demand. [3,4] It is reported that the global ethylene market is expected to grow from $190.29 billion in 2020 to $302.22 billion in 2025 with a compound annual growth rate (CAGR) of 7%, [5] and the ethanol market estimated at $87.4 billion in 2020, is projected to reach $137.4 billion with a CAGR of 6.7%. [6] Therefore, electrochemical reduction of the greenhouse gas CO 2 to produce ethylene and ethanol not only lowers the CO 2 emission, improves the atmospheric environment, and stores the renewable energy, but also has great economic benefits (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Co‐SAC coordinated with four nitrogen is an effective catalyst for HER, 44 but its molecular analogs such as cobalt porphyrin (CoP) and cobalt phthalocyanine (CoPc) are highly active in CO 2 ‐to‐CO electroreduction 45,46 . Table 1 shows the performance of some examples of SACs for CO 2 RR, such as Fe‐, 47–49,65–71 Co‐, 52,53,72,73 Ni‐, 74–87 Cu‐, 20,62,88–90 Zn‐, 58,59,91 and Sn‐based 60,61 ones 50,51,54–57,63,64 . Most of these SACs produced CO.…”
Section: Development Of Electrocatalystsmentioning
confidence: 99%
“…[4,24,25,28,33] So far, almost all attempts in tuning adsorption configuration of above-mentioned carbon/oxygen-containing intermediates were carried out through catalyst engineering,i .e., designing materials with as pecific electronic structure,which can lead to the desired adsorption ability toward the reactants and intermediates,thus determining the reaction pathway to target products. [6,34,35] However, such strategy has clear limitations:o no ne hand, it is effortconsuming to fabricate acatalyst with the exact desired active sites and electronic structures.O nt he other,m ethods for tuning intermediate status on designed catalysts are exceptional cases that can hardly be used as universal guidance on other catalysts.Itiscrucial to develop amore general strategy to control the adsorption configuration of intermediates by universal means.InCRR, many attempts have been made to control the product selectivity by adjusting the local reaction environment of the catalyst surface. [36][37][38][39] By applying af low cell reactor with ag as-diffusion-electrode (GDE), it was found that the concentration of local OH À ion has asignificant influence on the adsorption configuration of some complex intermediates (e.g., * CO-COH, * OCH 2 CH 3 )and C2 products selectivity.…”
Section: Introductionmentioning
confidence: 99%